IMMIGRATION INSTITUTION PERFORMANCE ACCOUNTABILITY BASED ON SMILE - Bobby Briando; Rasona Sunara Akbar; Agung Sulistyo Purnomo (Polteknik Imigrasi, 2018)
This study aims to develop the concept of immigration performance accountability based on the values of SMILE which is the acronym of “Simpatik, Mumpuni, Integritas, Lugas and Empati”. The study uses a Holistic paradigm, which considers theoretical and spiritual approach. The theoretical approach is carried out by the study of literatures while the spiritual approach is reflected through the understanding of the religious doctrine of truth. This paradigm tries to formulate the concept of holistic accountability. The results show that accountability does not only cover routine tasks and functions, but more importantly also the process of contemplation, meaning, and spirituality. Holistic accountability is the highest and the most abstract form of accountability that must be upholded by every public official i.e. a condition of being accountable not only to humans but also to the God